Analytic Hierarchy Process Based Selection of Leaders of Start-up Enterprises - Yuyang Yan; Cecilia A. Mercado (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The strength of leadership in the context of start-ups is closely related to the innovation and development of enterprises. The stronger the leadership of enterprises, the better the innovation and development of enterprises. Therefore, it is of great significance to study the leadership of enterprises. We can cultivate and improve enterprise leadership to meet enterprises' innovation and development needs in different situations. This paper uses four factors to evaluate enterprise leadership: strategic, communication, personal, and incentive. Assuming the relationship of various influencing factors, it establishes an analytic hierarchy process (AHP) model to select the best leaders among three kinds of enterprise leaders. This offers guidance that contributes to the theory and application of the AHP.